Influence of vitamin D security on the development of acute bacterial bronchitis in children of early age - Kraynya, H.; Крайня, Ганна Вікторівна (ДЗ «Запорізька медична академія післядипломної освіти МОЗ України», 2019)
The problem of acute inflammatory diseases of the bronchopulmonary system remains relevant in young children, because the addition of pathogenic flora can lead to recurrent forms of the disease and threatening bacterial complications in the future. The determination of factors influencing the development and course of acute bronchitis of bacterial etiology is of not only scientific, but also practical interest. The aim of the study: to assess the effect of vitamin D availability on the development of acute bronchitis of bacterial etiology in young children.
Keywords: тези доповідей